Hubungan Supervisi Infection Prevention Control Nurse (IPCN) Dengan Kepatuhan Perawat Dalam Menerapkan Standar Prosedur Operasional Universal Precaution - Wijaya, Leni; Siti Auliya Putri (Jurnal Kesehatan dan Pembangunan, 2024)
Universal Precaution is early warning in the form of control measures infections carried out by all health workers to prevent their occurrence infection with the principle that blood and body fluids are potentially infectious diseases originating from both patients and health workers. Objective This research is to determine the relationship between Infection Prevention Control supervision Nurse (IPCN) with nurse compliance in implementing standard procedures operational universal precautions. The research design used in This research is observational with a cross sectional approach. Population in this study were all inpatient and emergency room nurses at the hospital Specifically for Palembang Eyes in 2023. Total population in this study as many as 39 people, where the sampling technique used the total sampling. Data collection uses a questionnaire. Data analysis using univariate and bivariate analysis with Chi Square test. The research results were obtained that IPCN supervision in the high category was 34 respondents (87.2%), nurses' compliance in implementing the Universal Precaution SOP with high category as many as 31 respondents (79.5%). Chi Square test results were obtained p value 0.049 < ? 0.05 which means there is a relationship between IPCN supervision (Infection Prevention Control Nurse) with nurse compliance implementing universal SOPs precaution. It is hoped that the hospital can provide motivation and continuous training for nurses in universal matters precautions so that nurses can be more effective in preventing and controlling infections in the hospital and be able to apply the latest knowledge gained in training.